RESEARCH AND DEVELOPMENT FOR EARLY CHILDHOOD TEACHERS’ DESIRED COMPETENCIES OF THE CHILD DEVELOPMENT CENTERS UNDER LOCAL ADMINISTRATIVE ORGANIZATION CORRESPONDING THE CHANGE IN THE 21ST CENTURY EDUCATION: การวิจัยและพัฒนาสมรรถนะที่พึงประสงค์ของครูปฐมวัยของศูนย์พัฒนาเด็กเล็ก สังกัดองค์กรปกครองส่วนท้องถิ่น ที่สอดคล้องตามความเปลี่ยนแปลงทางการศึกษาในศตวรรษที่ 21 - Tangchitcharoenkhul, Rungnapa; Muangmoon, Saisamorn; Kijtorntham, Wichuda; Tangjitjaroenkun, Janpen (Journal of Education and Innovation, 2021)
The purposes of this research were 1) to formulate the components of desired competencies’ early childhood teachers of the child development centers under Local Administrative Organization corresponding the change in the 21st century education, 2) to examine indicators and research instruments of desired competencies’ early childhood teachers of the child development centers, 3) to evaluate desired competencies’ early childhood teachers of the child development centers of stakeholders, and 4) to study variables affecting desired competencies’ early childhood teachers of the child development centers. Data were collected by evaluation form from early childhood teachers, administrators, and parents. They were analyses using descriptive statistics, factor analysis and one-way ANOVA. The significant research findings were 1) Eighty-two related literatures were reviewed for synthesis the desired competencies’ early childhood teachers of the child development centers. There were 3 components of desired competencies’ early childhood teachers: 1.1) core competency consisted of 5 indicators (childhood’body of knowledge competency, instruction competency, research and development competency, learner development competency and self development competency, 1.2) non-core competency composed of 4 indicators (communication competency, moral and ethics competency, teamwork competency and academic service competency), 1.3) management competency composed of 4 indicators (leadership competency, environment management for learning support competency, environmental sanitary management competency and participation with community competency). 2) The result of the quality examination of desired competencies’ early childhood teachers of child development centers evaluated from experts and stakeholders found that they had appropriateness, feasibility and utility. 3)The evaluation results of desired competencies’ early childhood teachers of child development centers from stakeholders found that the component of core competency had the highest mean (mean=4.36, 4.31 and 4.28, respectively) followed by the non-core competency (mean=4.26, 4.19 and 4.19), and the component of management competency (mean=4.22, 4.16 and 4.11). 4) The factors affecting the desired competencies’ early childhood teachers of the child development centers were education level, experience in early childhood research and motivation for teacher developing.